ANALISIS PERPUTARAN MODAL KERJA DAN PENGARUHNYA TERHADAP SISA HASIL USAHA (SHU) PADA KOPERASI PEGAWAI NEGERI REPUBLIK INDONESIA (KPNRI) DI KOTA PALU - LESTARI, VANI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2016)
This study proves the influence of working capital turnover (turnover of cash, accounts receivable turnover, inventory turnover) on net income (SHU) at the Civil Servants Cooperative of Republic of Indonesia (KPNRI) in Palu in 2011-2014. The data in this study is time series data in the form of financial statements, which consist of data on the balance sheet and profit/loss or SHU in four consecutive years of 2011-2014 of KPNRI in Palu City. Research sample is 12 cooperatives selected with purposive sampling technique. Model of analysis is multiple linear regressions analysis. The research proves that rotation of working capital includes cash turnover, accounts receivable turnover, inventory turnover simultaneously have significant influence on the SHU with f-value of 5.951 and significance level of 0.002 <? 0.05. Partially, cash turnover positively has significant influence on SHU with t-value of 2.184 with a significant value of 0.034 <? 0.05, receivable turnover has non- significant influence on the SHU with t-value of 2.595 with significance value of 0.180> ? of 0.05, inventory turnover significantly has negative influence on SHU with t-value of -2.650 and significance value of 0.004 <? 0.05.